Profesionalisme Nadzir dalam Meningkatkan Kepercayaan Wakif di Lembaga Wakaf - Vina Fithriana Wibisono; Syamsuri Syamsuri; Muchamad Zainur Rohman (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract, The success of waqf management lies in the existence of nadzir in maximizing the role of waqf, therefore the existence and quality of nadzir must receive more attention, from both individual, organizational and legal institutions. In Indonesia, the majority of waqf is managed by individual nadzir (66%) and are traditional, so the waqf cannot be managed professionally, the professionalism of nadzir in addition to waqf management to improve the social and economic welfare of the community as well as a means to maintain the trust of the wakif, the trust of the waqf wakif is influenced by the professionalism of the nadzir in managing waqf, professionals in managing waqf assets are required to refer to modern management principles, in waqf, waqf managers or nazir need management in carrying out their duties, among nadzir professionalism in managing waqf is waqf management with transparency and accountability, so that the wakif participate in monitoring the development of waqf, either from reports or others.